Insights on the solvatochromic effects in N-doped yellow-orange emissive carbon dots. (15th November 2018) - Arshad, Farwa; Pal, Ayan; Rahman, Md Atiur; Ali, Maroof; Khan, Javed Alam; Sk, Md Palashuddin
Abstract : We have demonstrated a rapid and facile synthetic method to prepare N-doped Cdots that has excitation independent-emission in yellow-orange region. The Cdots showed solvatochromic behavior in different solvents due to change in solvent polarity illustrating n → π* transition (edge band). Abstract : Carbon dots (Cdots), a new class of carbogenic nanomaterial with exceptional fundamental characteristics, have perplexed researchers since their discovery. Their high quantum yield and tunable emission property with high sensitivity towards the local environment makes these nanomaterials suitable for multiple applications. However, the exact transition mechanism behind the exceptional photophysical behavior of Cdots is still a subject of debate. Cdots interactions with local environment and corresponding photophysics provide valuable intuition on the electronic transition inside the structure. Herein, we report microwave assisted one step synthesis of nitrogen (N) doped Cdots with yellow-orange emission. As-synthesized, the N-doped Cdots exhibit excellent solvatochromic effect in a wide range of solvents, thus giving a comprehensive elucidation towards electronic transitions inside the carbon nanostructure. We found that H-bonding interactions did not have any stabilization effect on the photo excited state. Detailed analysis revealed that non-specific interactions due to the dipolar/polarizability effect of solvents, the resulting stabilization of the excited state and the charge transfer process involved with the core, edge state and surface state help tune the polarity based-photophysical property of the present Cdot system.